Evaluation of Soil Characteristics and Environmental Parameters of Arid-Semi Arid (Desert) Truffles from Eastern Turkey - Akyüz, Mehmet; Kırbağ, Sevda; Gürhan, Yasemin; Bircan, Burak (My University, 2017)
The ecological characteristics of arid-semi arid truffles from Eastern Turkey were investigated. The habitat and climate characters of the collection sites were determined and soil samples from localities were analysed. The light strength, temperature, humidity, air flow and air velocity at the areas were recorded to be 17.7 klux to 303.9 klux, 7.8ºC to 24.3ºC, 11.9% to 43.2%, 3702.6 ft3/min to 8941.6 ft3/min, and 3.6 km/h to 16.9 km/h, respectively. Environmental parameters match the climatic requirements, which is normal for the region when spring is concerned. The soil samples contained 42.59% to 91.46% sand, 4.49% to 38.43% clay, 4.04% to 25.91% silt, 8.54% to 57.41% silt-clay. The soil types included sandy, sandy-loam, clay-loam, loam-sand, sandyclay-loam types. The soil examples were understood to have alkaline characteristics and had a lime content. The level of organic material and nitrogen was low, whereas the amounts of phosphorus, potassium and sodium were high. Based on our studies and observations, it is possible to claim that habitat, host plant, climate, and soil types are as important as precipitation for the healthy growth of truffles.
Keywords: Mantar Bilimi; Çevre Bilimleri; Ekoloji; Ziraat; Toprak Bilimi